Elder abuse the real definition : abusive physical interactions. - Stevens, Georgia L.; University of Maryland at Baltimore. Video Press (Baltimore, Md. : Video Press, University of Maryland School of Medicine, 2000)
(Producer) Care providers discuss types of unacceptable physical interactions: use of force when an older person cannot or will not cooperate: grabbing, hitting, or pushing a resident; and rough manner while providing care.
Presented by Georgia Stevens.
Keywords: Elder Abuse -- prevention & control; Aged; Long-Term Care -- methods; Nurse-Patient Relations